PENGARUH LEADER MEMBER EXCHANGE DAN SELF EFFICACY KARYAWAN TERHADAP EMPLOYEE VOICE BEHAVIOR DI PT. INTERNASIONAL PRIMA COAL SAMARINDA - ., Rahmaniah Walidi (MOTIVASI, 2018)
This study aims to find out whether there is an influence of Leader Member Exchang and Employee Self Efficacy on Employee Voice Behavior. so there are 3 influences that will be investigated in this study, namely: 1) Leader Member Exchang; 2) Self Efficacy of employees; 3) Employee Voice Behavior. This research was conducted on employees of PT. Internasional Prima Coal Samarinda where the company is engaged in coal mining. The subjects in this study were 51 employees. sampling in this study using saturated sampling technique where all populations are used as samples because of the relatively small population. The data analysis technique used is multiple linear regression analysis. The results of the regression analysis of this study are R = 0.156, R2 = -0.16, F regression = 0.598, it shows that there is no positive and significant influence from Leader Member Exchang and employee Self Efficacy on Employee Voice Behavior.